Bimetallic Cu(i) complex with a pyridine-bridged bis(1, 2, 3-triazole-5-ylidene) ligand. Issue 13 (1st March 2016) - Iwasaki, Haruka; Teshima, Yuta; Yamada, Yuji; Ishikawa, Ryuta; Koga, Yuji; Matsubara, Kouki
Abstract : Expanded π-conjugated system catalyst for hydroboration of alkenes. Abstract : A dinuclear copper(i ) complex bearing a mesoionic carbene ligand has been prepared from the corresponding silver analogue and its structure determined spectroscopically. The results revealed that two Cu(i ) halide salt molecules were bound to the carbon atoms of the pyridine-bridged bis(triazolylidene) moieties rather than the pyridine. Cyclic voltammogram measurements revealed that the two Cu(i ) centres underwent a stepwise oxidation, suggesting that both the triazolylidene rings of the ligand could be on the same expanded π-conjugated system. The catalytic hydroboration of styrene derivatives with bis(pinacolato)diborane in the presence of this complex allowed for the β-selective formation of the corresponding alkylboronate esters.